Surface growth of highly oriented covalent organic framework thin film with enhanced photoresponse speed. Issue 112 (29th October 2015) - Chen, Ying; Cui, Haijun; Zhang, Jianqi; Zhao, Kun; Ding, Defang; Guo, Jun; Li, Lianshan; Tian, Zhiyuan; Tang, Zhiyong
Abstract : An oriented photoconductive COF film was synthesized by in situ growth method. Abstract : An oriented photoconductive COF film was synthesized by in situ growth method. The as-prepared oriented film shows greatly improved photoresponse speed as compared with randomly oriented films. This work demonstrates the importance of controlling the orientation of photo conductive COF films in order to facilitate charge transport and opens the door to prepare oriented COF films for optoelectronic devices.